GAMBARAN PENGETAHUAN, SIKAP DAN PERILAKU KELUARGA DALAM MEMILIH OBAT BEBAS SAAT SAKIT DI DUSUN NGRANDU DESA POMAHAN KECAMATAN BAURENO KABUPATEN BOJONEGORO - MULYANI, SRI; FIRMANSYAH, ANDI AGUNG; Hasyim, Abd Wakhid (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2015)
ABSTRACTTreatment (self medication) is an effort that most people do families to deal with complaints or symptoms of the disease, before they decided to seek help from a health care facility or health care workers. The purpose of this study was to identify the knowledge, attitudes and behavior in choosing a drug-free families when sick.This descriptive study design with the entire population is families in the hamlet village Ngrandu Pomahan Baureno District of Bojonegoro 2014 some 95 people. With purposive sampling technique obtained a sample of 38 respondents. Data collection by questionnaire, and then processing the data with the editing, coding, scoring and tabulating and analyzing the data with the percentage.The results of this study are more than most have less knowledge of 20 respondents (52.63%), more than most have unfavorable attitudes by 22 respondents (57.89%) and more than most have negative behavior as much as 24 respondents (63.16% ).The conclusion of this study is the respondent in the hamlet village Ngrandu Pomahan Baureno District of Bojonegoro 2014, more than most have less knowledge, more than most have unfavorable attitudes and more negative behavior than most have. So expect respondents increase knowledge about drug-free election when sick.Â Â Â Keywords: Knowledge, Attitude, Behavior, Family, Drug Free.